2008
DOI: 10.1308/003588408x242015
|View full text |Cite
|
Sign up to set email alerts
|

Managing the 2-Week Wait for Breast Patients

Abstract: Ann R Coll Surg Engl 2008; 90: 69-71 69The 2-week wait for breast cancer was introduced by the UK Government on 1 April 1999. 1 This initiative was recognised in the NHS Cancer Plan and further targets were subsequently incorporated. 2Ever since the inception of 2-week wait, numerous studies have been conducted looking at various aspects of this service. [3][4][5][6][7][8][9][10][11][12][13][14] Published data suggest that the 2-week wait system and triple assessment at one fast-track clinic visit is an out-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Our study registered data which were significantly higher in terms of GP referral (around 60%) and cancer detection rates (around 30%), and similar in terms of adherence to referral guidelines. In breast cancer, the 5-year study (period 1999–2005) conducted by Singhal et al (2008) covered 6678 patients, 46.7% of the total seen in the period. The cancer detection rate was 16.4%, and guideline adherence was 71.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Our study registered data which were significantly higher in terms of GP referral (around 60%) and cancer detection rates (around 30%), and similar in terms of adherence to referral guidelines. In breast cancer, the 5-year study (period 1999–2005) conducted by Singhal et al (2008) covered 6678 patients, 46.7% of the total seen in the period. The cancer detection rate was 16.4%, and guideline adherence was 71.9%.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] However, for common tumours, the incidence within primary care is reasonably high so there is an a priori reason to assume that urgent referrals will result in a diagnosis of malignancy in a significant proportion of cases. Table 2 Summary of referred and observed criteria…”
Section: Discussionmentioning
confidence: 99%
“…Similar strategies have been adopted in other malignancies, and recent published reviews of workload changes and outcome data relating to the 2-week wait criteria of these cancers have shown a wide range of diagnostic efficiency. In breast cancer, approximately 10-20% of these urgent referrals are shown to have malignancy, [7][8][9] with a similar rate of 10% for colorectal cancer. 10,11 Some authors have indicated a decrease in 'standard' referrals since the introduction of the system, with a commensurate rise in urgent referrals, which has necessitated a shift in practice towards making more clinical appointments available for suspected cancer referrals at the expense of routine work.…”
mentioning
confidence: 99%
“…The diagnostic yield of malignancy has also varied widely from 9.4% to 16.4% for bowel and breast cancer, respectively, [2, 3]. One study looking into urological malignancies [4] found that 11 out of 35 patients (31.4%) referred with a high PSA had prostate cancer, but most cases were beyond cure.…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable controversy about the benefits of two-week wait clinics with some claiming that they will not improve the diagnosis of patients with malignancy and others that they will delay diagnosis and management of other nonmalignant conditions. The diagnostic yield of malignancy has also varied widely from 9.4% to 16.4% for bowel and breast cancer, respectively, [ 2 , 3 ]. One study looking into urological malignancies [ 4 ] found that 11 out of 35 patients (31.4%) referred with a high PSA had prostate cancer, but most cases were beyond cure.…”
Section: Introductionmentioning
confidence: 99%